Dialectics of Archaic and Modern in the Axiology of Modern Law - F. P. Furman (Теоретическая и прикладная юриспруденция)
The characteristics, structures and hierarchies of the value world are considered. The ways of cognition of value and its ontological status are identified. The nature and specificity of value judgments is given. The study examines the problem of theoretical and conceptual positions, principles and methods of law and their axiological significance; the issues of modern social economics and legal nature are analyzed; the axiological significance of the principles of civil law in modern conditions is determined. Theoretical and practical aspects of the axiology of the principles of modern law are established and disclosed; it was concluded that the axiological significance of the principles of law is constant and stable and does not depend on historical or socio-economic conditions; it has been confirmed that legal axiology as a research type of legal philosophy is capable of elevating value transformations in the system of legal reality to the level of self-reflection of law as a form of social consciousness.